O papel do enfermeiro como educador junto a cuidadores familiares de pessoas com AVC. - Bocchi, Silvia Cristina Mangini (FapUNIFESP (SciELO), 2004)
This article was written based on bibliographical research aiming at making a thematic analysis of the production of knowledge in newspapers and magazines about the nurse's role as an educator toward people who care for BVA (brain vascular accident) patients. The analysis gathered articles published in the 80's and 90's, from the Medline, Lilacs and Cinahl databases. Content analysis was the methodological background that allowed the organization of knowledge in two categories: educational intervention in the acute stage and the post-discharge support.
The nurse's role as an educator toward people who care for BVA patients
Keywords: caregiver; cerebrovascular accident; education; human; nurse attitude; nursing; review; Caregivers; Cerebrovascular Accident; Humans; Nurse's Role